OP0079 Pharmacodynamic Changes in Gene Expression Observed in Two Phase 3 Trials of Baff Blockade with Tabalumab in SLE. (9th June 2015) - Hoffman, R.; Merrill, J.T.; Alarcόn-Riquelme, M.E.; Petri, M.; Dow, E.R.; Nantz, E.; Nisenbaum, L.K.; Schroeder, K.M.; Komocsar, W.J.; Perumal, N.B.; Rocha, G.V.; Higgs, R.E.
Abstract : Background: RNA gene expression profiling was performed on 1, 760 SLE patients randomly selected from Illuminate Trials 1 & 2 which studied the anti-BAFF, IgG4 monoclonal antibody, tabalumab, for efficacy in SLE (Isenberg D., et al. ACR Boston 2104). The baseline disease activity and clinical characteristics were balanced across treatment and placebo groups in both Trial 1 (N=1164) & 2 (N=1124). The primary endpoint of SRI-5 was not met in Trial 1 but was met in Trial 2 for the 120mg Q2week (W) dose (p=0.002). Objectives: The present study characterized baseline and pharmacodynamic (PD)-induced changes in gene expression from these two cohorts of SLE patients. Methods: Whole blood was collected in Tempus tubes at baseline, weeks 16 and 52. RNA was extracted and analyzed using Affymetrix HTA 2.0 whole genome microarrays. Serum levels of IgG anti-dsDNA antibodies (abs) were measured by ELISA. Serum complement components C3 and C4 were measured by nephelometry and B cells enumerated using flow cytometry. Statistical analyses to identify PD-induced gene changes were conducted with Q2W and Q4W cohorts using a mixed effects model with relative gene expression as the response and inclusion of baseline clinical covariates. Results: Statistically significant PD changes were observed in both trials in the Q2W and Q4W 120mg dosing arms compared to placebo for the following biomarkers: anti-dsDNA abs, C3 & C4, total serum IgG, IgM & IgA, and peripheral blood B cell number (all with p<0.001). Changes in gene expression in tabalumab treated patients were compared to placebo in 422 randomly selected patients at baseline, weeks 16 and 52. Statistically significant changes were identified in 410 genes (false discovery rate qval<0.20 Trial 1 and p<0.20 Trial 2) including: plasma cell markers, B cell markers, TNF superfamily members, Fc & Fc-like receptors, complement receptors and a pain receptor, SCN3A. There were no changes in monocyte or neutrophil specific markers. A group of 34 pre-specified interferon responsive genes (IRG) were examined and baseline elevation of IRG was significantly associated with elevated anti-dsDNA abs and decreased levels of C3 & C4. B cell number as measured by flow cytometry correlated with gene expression of B cell-associated genes including CD19. PD changes in predefined B cell and plasma cell genes were observed in the treatment groups and associated with changes in anti-dsDNA abs, serum Ig and complement levels, and cell number; however, treatment with tabalumab was not associated with changes in IRG or BAFF gene expression. Conclusions: Pharmacodynamic changes associated with tabalumab treatment included anti-dsDNA abs, complement components C3 & C4, serum IgG, IgA & IgM, and B cell numbers. Statistically significant changes were observed in 410 genes, broadly consistent with the mechanism of BAFF blockade. Changes in expression of a number of additional genes were unexpected and suggest that these may be of importance in anti-BAFF drug response. The data here confirm previous smaller studies that a Type I interferon signature may represent a distinctive subset of SLE patients. Disclosure of Interest: R. Hoffman Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, J. Merrill: None declared, M. Alarcόn-Riquelme: None declared, M. Petri: None declared, E. Dow Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, E. Nantz Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, L. Nisenbaum Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, K. Schroeder Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, W. Komocsar Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, N. Perumal Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, G. Rocha Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, R. Higgs Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company